Pengembangan Kreativitas Mahasiswa dengan Menggunakan Metode Brainstorming dalam Mata Kuliah Kewirausahaan - Asni Harianti; Yolla Margaretha (Jurnal Manajemen Maranatha, 2014)
Creativity is a factor that supports a person in entrepreneurship.Entrepreneurship should be able to increase the cognitive adaptation that has the ability to think creatively to create new ideas or solutions to solve problems and find opportunities. Students who take the course as an aspiring entrepreneurEntrepreneurship, creativity needs to be built to be able to practice how entrepreneurship. One of the efforts to develop the ability to think creatively in teaching Entrepreneurship performed using the method of group brainstormingmethod to get various ideas and new solutions. The research of brainstorming method is using experimental design. This research applied to the Department of Management students who take courses in Entrepreneurship odd semester2013/2014. The results showed that there was a significant increase in student creativity after getting treatment method of brainstorming, but there is no difference in the development of student creativity in the group treated with the method ofbrainstorming untreated group (traditional method).Key words: Creativity, brainstorming